2022
DOI: 10.1016/j.ijid.2021.12.332
|View full text |Cite
|
Sign up to set email alerts
|

Colombian Ocular Infectious Epidemiology Study (COIES): Herpes Zoster Ophthalmicus prevalence and sociodemographic characterization, 2015-2019

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Emma et al’s study 13 analyzed HZO patients at the Massachusetts Eye and Ear Infirmary (MEEI), dividing the cases into two groups: 71 cases in 2007 vs 195 cases in 2013, with the average age of the latter group dropping significantly by almost six years. Carlos et al’s recent study 14 also analyzed the incidence rate of HZO in Columbia and found that its proportion increases with age in a total of 100,000 residents. We speculate that herpes zoster is showing a trend of getting younger.…”
Section: Discussionmentioning
confidence: 99%
“…Emma et al’s study 13 analyzed HZO patients at the Massachusetts Eye and Ear Infirmary (MEEI), dividing the cases into two groups: 71 cases in 2007 vs 195 cases in 2013, with the average age of the latter group dropping significantly by almost six years. Carlos et al’s recent study 14 also analyzed the incidence rate of HZO in Columbia and found that its proportion increases with age in a total of 100,000 residents. We speculate that herpes zoster is showing a trend of getting younger.…”
Section: Discussionmentioning
confidence: 99%
“…HZ and HZO are more common in women than in men [ 11 , 18 20 ]; in the analysis by Kong et al [ 16 ], the annual incidence of HZO in women and men was estimated to be 44.5 and 33.1 cases per 100,000 person-years, respectively.…”
Section: Epidemiologymentioning
confidence: 99%